Synthesis of Adipic Acid Oxidized by H2O2-Silicotungstic Acid Under Ultrasonication - Lin, Zhi-Ping; Wan, Li (Asian Journal of Chemistry, 2013)
A green synthesis of adipic acid from cyclohexene oxidized by H2O2-silicotungstic acid was carried out in 92 % yields at 30 ºC within 4 h under ultrasound irradiation.